Analysis of Factors Affecting the Firm Value and Profitability as a mediation on Heatlh Company Sector in BEI 2017-2022 - Nor Fauziyah; Muazaroh Muazaroh (Riviera Publishing, 2025)
Firm value in healthcare companies is influenced by financial decisions, yet prior studies show inconsistent results, particularly post-pandemic. This research examines how investment decisions, capital structure, liquidity, and dividend policy affect firm value, with profitability as a mediator. The research aims to analyze the direct and mediated effects of financial ratios on firm value in Indonesian healthcare firms (2017–2022). The research used quantitative analysis of 61 observations from 15 IDX-listed healthcare companies using multiple regression and Sobel mediation tests. Profitability significantly enhances firm value (?=10.004, p<0.05) and fully mediates investment decisions and liquidity, while partially mediating capital structure (DER: ?=-1.057, p<0.05). Capital structure negatively impacts firm value, whereas dividend policy shows an adverse but insignificant effect. Healthcare firms should prioritize profitability optimization and debt caution to boost investor confidence. Future research should expand to other sectors and integrate macroeconomic variables for broader applicability.